The Difference of Students' Learning Activities and Output Due to Problem Based Teaching Model by Using Practicum Method With Video Observation Method - Sugiharini, Sugiharini; Ridlo, Saiful; Priyono, Bambang (FMIPA UNNES, 2019)
This study aims to describe the difference of students’ activity and learning outcome between students who do problem based teaching model practicum method and students who do problem based teaching model video observation method. This study is quasi-experimental with posttest-only design. Population of this research is the whole of grade VIII students. The samples of the study are VIIID (experimental class 1) and VIIIC (experimental class 2) which are taken using cluster random sampling technique. The result of this study is the class who did problem based teaching model practicum method got post-test result 77,31. While the class who did problem based teaching model video observation method got 70,75. According to Mann-Whitney test with Asymp. Sig (2-tailed) 0,002 < 0,05, it can be assumed that there is significant difference on students’ learning outcome between class who did problem based teaching model practicum method and class who did problem based teaching model video observation method. The average of students who are very active and active on the experiment class 1 is 85,15% and experiment class 2 is 78,90%. Based on the study result, it shows that there is difference of activity and learning outcome between students who did problem based teaching model practicum method and problem based teaching model video observation method.